Political trust and elite closure: Evidence from Latin America - Ortiz-Inostroza, C (SAGE Publications Ltd, 2026)
We examine how the degree of social closure among political elites shapes mass-level political trust in Latin America, a region marked by historically closed elites and persistently low trust. Building on contrasting perspectives, we argue that elite closure undermines citizens’ trust, but its influence also depends on a country’s long-term patterns of closure. In contexts where elites have been highly closed over time, further increases are expected to erode trust. In more open systems, by contrast, closure may be positively associated. Our analysis combines LAPOP data (2004–2018) with PELA-USAL elite indicators in a large-N comparative framework. Estimates from hierarchical models indicate that elite closure—characterized by legislative re-election rates and family ties in politics—significantly reduces political trust. However, these results are heterogeneous: rising closure erodes trust only in countries where elites have historically been highly closed, highlighting the context-dependent role of elite composition in shaping citizens’ political trust. © The Author(s) 2026